CONSERVATION OF THE ENVIRONMENT AND ECOLOGICAL HABITS IN ENVIRONMENTAL AWARENESS AMONG ADOLESCENTS IN THE PERUVIAN JUNGLE - Guadalupe-Zevallos, Oscar Gustavo (2023)
Environmental education has emerged as a strategy to provide solutions to the climate crisis affecting the world, in order to stimulate the development of environmental awareness and promote ecological habits and environmental conservation. In this context, a research was carried out with the objective of determining the influence of environmental conservation and ecological habits on environmental awareness in a sample of 92 high school students of the Alipio Ponce Educational Institution in the Tambopata region -Madre de Dios. The study adopted a basic, non-experimental, cross-sectional and causal correlational design. Three questionnaires were applied to assess the variables environmental conservation, ecological habits and environmental awareness. For each, three dimensions were assessed. The results showed that the variables ecological habits and environmental conservation influence the development of environmental awareness. It is concluded that students are motivated and willing to address environmental issues, but with regular knowledge, which may have a negative impact on the development of pro-environmental attitudes. It is recommended to implement pedagogical strategies that articulate theory with practice reflected in daily situations.